ANALYSIS OF THE EFFECTIVENESS OF XP-ENDO FINISHER R IN ORTHOGRADE ENDODONTIC RETREATMENT - Irina Tsenova-Ilieva; Violeta Dogandzhiyska; Emilia Karova (Peytchinski Publishing, 2022)
Background: Removal of the root canal filling material in the course of the endodontic retreatment is achieved by the use of various instruments and techniques. Purpose: The aim of this article is to systematically analyze published in vitro investigations over a five-year period of time (2018-2022), assessing the efficacy of the XP-Endo Finisher R file as a supplementary approach in orthograde endodontic retreatment. Materials and methods: The literature data was acquired through PubMed - MEDLINE, The Cochrane Library and Science Direct database and hand web search, then the articles were assessed by three independent reviewers. Results: An overall number of eighteen papers out of 108 titles met the eligibility criteria and were finally chosen for quantitative synthesis. Most of the studies affirmed the effectiveness of XP-Endo Finisher R by means of microcomputed tomography. Shaping with the file is not able to guarantee root canal walls free of remnants. Conclusions: XP-Endo Finisher-R is an effective supplementary approach in endodontic retreatment procedures. Nonetheless, it is rarely reported to achieve the complete removal of the root canal filling material. Micro-CT is a reliable, non-invasive analytical tool that can accurately measure the volume and the percentage of the remaining root canal fillings.